Surgical results of decompressive craniectomy in very young children: A level one trauma centre experience from India. (6th December 2015) - Prasad, G. Lakshmi; Gupta, Deepak Kumar; Mahapatra, Ashok Kumar; Sharma, Bhawani Shankar
Abstract: Introduction : Literature remains sparse regarding decompressive craniectomy (DC) in traumatic brain injury (TBI) in very young children. This study analysed the indications, complications and outcome of young children undergoing DC for TBI at our institute. Study design : Retrospective. Observations : The total number of patients was 71. Mean age was 1.6 years. Mean duration from injury to surgery was 11.9 hours (range = 3–80 hours). Around 50% had severe head injury. Intracranial pressure (ICP) monitoring was done in 33 patients. Mean ICP was 22.2 mm Hg (range = 9–50 mm Hg). The threshold ICP for surgery was 15 mm Hg. Perioperative mortality was 50% each for severe TBI (18/36) and diffuse cerebral edema (7/14), and 58% for infants (4/7). Ninety per cent of expired patients had ICP > 20 mm Hg. Mean follow-up duration was 19.6 months (range = 2–42 months). Except one, all survivors had good-to-excellent outcomes (Glasgow outcome scale extended; GOS-E = 7–8). Conclusions : Decompressive craniectomy offers a survival advantage in almost 50% of young children with severe TBI and should be used judiciously. The highest mortality was within the 1st week of surgery. The cut-off limit of 20 mm Hg for surgical decompression might not be applicable to young children and a low threshold ICP needs to be considered. Factors associated with increased mortality are high opening ICP (>20 mm Hg), GCS <8, diffuse cerebral oedema and infant age group. Timing of DC remains crucial. Further prospective studies are necessary to optimize the timing and ICP limit for surgical decompression.